2013
DOI: 10.1039/c3an36817c
|View full text |Cite
|
Sign up to set email alerts
|

Profiling intact steroid sulfates and unconjugated steroids in biological fluids by liquid chromatography-tandem mass spectrometry (LC-MS-MS)

Abstract: Within the combined DFG research project "Sulfated Steroids in Reproduction" an analytical method was needed for determining sulfated and unconjugated steroids with highest specificity out of different biological matrices such as aqueous solution, cell lysate and serum. With regard to this analytical challenge, LC-MS-MS presents the technique of choice because it permits (1) analysis of the intact steroid conjugate, (2) allows for simultaneous determination of multiple analytes (profiling, targeted metabolomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…Mass spectrometer conditions were as reported before ( 16 ). Briefl y, the capillary temperature and the vaporizer temperatures were set to 270 and 350°C, respectively.…”
Section: Msmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometer conditions were as reported before ( 16 ). Briefl y, the capillary temperature and the vaporizer temperatures were set to 270 and 350°C, respectively.…”
Section: Msmentioning
confidence: 99%
“…In 2003, Liu, Griffi ths, and Sjövall ( 15 ) provided a method to obtain a more detailed profi ling of sulfated steroids in human plasma. Recent work has focused on extending the number of sulfated steroids analyzed simultaneously in a single LC-MS analysis ( 16,17 ).…”
mentioning
confidence: 99%
“…Measurement of free and sulfated steroids by liquid chromatography-tandem mass spectrometry A 4 , testosterone, PREGS, DHEAS, E 1 S, and E 2 S, were quantified in boar heparin plasma using isotope dilution liquid chromatography-tandem mass spectrometry (LC-MS/MS), as previously published (Galuska et al 2013). Briefly, the samples were mixed and equilibrated with deuterated internal standards (d 4 E2S, d 4 PREGS, d 3 T, d 7 -4A, and d 6 DHEAS).…”
Section: Sample Collection From Hcg-stimulated Boarsmentioning
confidence: 99%
“…The sulfated steroids can be analyzed as intact molecules ( 21 ) without any need for derivatization, providing important structural information, e.g., position of the sulfate in the structure. Of note, sulfated steroids have very specifi c transitions in MS/MS experiments (21)(22)(23).…”
Section: Experimental Procedures For the Identifi Cation Of The Steromentioning
confidence: 99%
“…By means of non-targeted MS tools, the comparison of serum from RXLI patients with serum from The mass spectrometer was operated fi rst in negative parent ion scan mode (precursor ion scan mode) with a product mass of 96.9, a scan range of m/z 30-650, a scan time of 1 s, and collision energy of 45 V. The same parameters were applied to a product mass of 79.9. These product masses were selected taking into consideration previous studies, which showed that 96.9 and 79.9 are the most common fragmentation products of sulfated steroids, with the exception of estrogen sulfates (21)(22)(23).…”
Section: Experimental Procedures For the Identifi Cation Of The Steromentioning
confidence: 99%